Expression quantitative trait loci in ABC transporters are associated with survival in 5-FU treated colorectal cancer patients. (10th January 2020) - Vymetalkova, Veronika; Rosa, Fabio; Susova, Simona; Bendova, Petra; Levy, Miroslav; Buchler, Tomas; Kral, Jan; Bartu, Linda; Vodickova, Ludmila; Hughes, David J; Soucek, Pavel; Naccarati, Alessio; et al.
Abstract: The chemotherapeutic efficacy in colorectal cancer (CRC) is limited due to the inter-individual variability in drug response and the development of tumour resistance. ATP-binding cassette (ABC) transporters are crucial in the development of resistance by the efflux of anticancer agents from cancer cells. In this study, we identified 14 single nucleotide polymorphisms (SNPs) in 11 ABC transporter genes acting as an expression of quantitative trait loci (eQTLs), i.e. whose variation influence the expression of many downstream genes. These SNPs were genotyped in a case–control study comprising 1098 cases and 1442 healthy controls and analysed in relation to CRC development risk and patient survival. Considering a strict correction for multiple tests, we did not observe any significant association between SNPs and CRC risk. The rs3819720 polymorphism in the ABCB3/TAP2 gene was statistically significantly associated with shorter overall survival (OS) in the codominant, and dominant models [GA vs. GG, hazard ratio (HR) = 1.48; P  = 0.002; AA vs. GG, HR = 1.70; P  = 0.004 and GA + AA vs. GG, HR = 1.52; P  = 0.0006]. Additionally, GA carriers of the same SNP displayed worse OS after receiving 5-FU based chemotherapy. The variant allele of rs3819720 polymorphism statistically significantly affected the expression of 36 downstream genes. Screening for eQTL polymorphisms in relevant genes such as ABC transporters that can regulate the expression of several other genes may help to identify the genetic background involved in the individual response to the treatment of CRC patients.